Donor cornea transfer from Optisol GS to organ culture storage: a two‐step procedure to increase donor tissue lifespan. (16th March 2012) - Haug, Kristiane; Azqueta, Amaya; Johnsen‐Soriano, Siv; Shahdadfar, Aboulghassem; Drolsum, Liv K.; Moe, Morten C.; Røger, Magnus T.; Romero, Francisco J.; Collins, Andrew R.; Nicolaissen, Bjørn
Abstract. Purpose: Storage time for donor corneas in Optisol GS is limited compared to Eye Bank Organ Culture (EBOC). We here examine the epithelium on donor corneoscleral rims after primary storage in Optisol GS and subsequent incubation in EBOC. Methods: Morphology was monitored by light and electron microscopy, expression of phenotypic and genotypic markers by immunohistochemistry and RT‐PCR and changes in oxidative lipid and DNA damage by ELISA and COMET assay. Results: A prominent loss of cells was observed after storage in Optisol GS. After maintenance in EBOC, spreading apical cells were Occludin+, while the staining for E‐cadherin and Connexin‐43 was less intense. There were an upregulation of Occludin and a downregulation of E‐cadherin and Connexin‐43. Eye Bank Organ Culture was associated with an ongoing proliferative activity and a downregulation of putative progenitor/stem cell marker ABCG2 and p63. Staining for 8‐OHdG and Caspase‐3 did not increase, while levels of malondialdehyde and number of DNA strand breaks and oxidized bases increased. Conclusions: This dual procedure should be pursued as an option to increase the storage time and the pool of available donor corneas. The observed downregulation of markers associated with stemness during EBOC is relevant considering the potential use of donor epithelium in the treatment of ocular surface disorders.